THE EPISTEMOLOGY OF SHARAF SCIENCE: A HISTORICAL OVERVIEW AND ITS CONTRIBUTION TO ARABIC LINGUISTICS - Ahmad Sirfi Fatoni; Muhammad Jamil (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Arabic morphology constitutes a fundamental branch of classical Arabic linguistics, focusing on morphological word transformation (tashrif) and derivational morphology. Despite more than a millennium of development, epistemological inquiry into ilmu sharaf — concerning its sources of knowledge, methods of rule formation, and scientific validity — remains considerably limited in contemporary academic literature, with existing studies tending toward normative and pedagogical orientations that neglect its fundamental philosophical dimensions. This article aims to examine the epistemology of ilmu sharaf from the philosophy of science perspective, tracing its historical genealogy from the early Islamic codification period through to modern Arabic linguistics, and analyzing its contributions to contemporary Arabic morphology. The research employed a qualitative library research method with historical, epistemological, and comparative-linguistic approaches, utilizing critical analysis of relevant primary and secondary sources. The findings reveal that ilmu sharaf possesses a robust epistemological foundation derived from the Qur'an, hadith, classical Arabic fushah poetry, and qiyas (analogical reasoning), and was developed through the methods of sima' (documentation), istinbath (inference), and ta'lil (rational justification) by linguists of the Bashrahn and Kufahn schools. Ontologically, its subject matter is morphological word transformation that produces semantic change; axiologically, it functions to preserve Arabic linguistic purity and facilitate Qur'anic comprehension. The contributions of ilmu sharaf to modern Arabic linguistics are demonstrably significant, particularly in the development of root-and-pattern morphology theory, derivational semantics, and Arabic natural language processing (NLP). These findings indicate that the classical sharaf tradition is not merely historically relevant but also carries important methodological implications for contemporary Arabic computational linguistics.